BONE REMODELING IN NORM AND IN PRIMARY OSTEOPOROSIS: THE SIGNIFICANCE OF BONE REMODELING MARKERS - G. M. Nurullina; G. I. Akhmadullina (Архивъ внутренней медицины)
Osteoporosis is a systemic skeletal disease is characterized by low bone mass and microarchitectural deterioration of bone tissues, leading to bone fragility and low-energy The incidence of osteoporosis has risen because the life expectancy of the population has been increasing . Osteoporosis is an extremely common disease: osteoporosis affects more than 200million people worldwide and causes more than 8.9 million fractures. In Russia, among people aged 50 years and older, osteoporosis is diagnosed in 34% of women and 27% of men. The social significance of osteoporosis is determined by its consequences — fractures of the bones of the peripheral skeleton and vertebral fractures, leading to high material costs and causing a high level of disability and mortality. The normal physiological process of bone remodeling involves a balance between bone resorption and bone formation. In osteoporosis, this process becomes unbalanced, resulting in gradual losses of bone mass and density due to enhanced bone resorption and/or inadequate bone formation. Several signaling pathways underlying primary osteoporosis have been identified, such as the osteoprotegerin/ receptor activator of nuclear factor kappa-B (RANK)/RANK ligand(RANKL), bone morphogenetic proteins, canonical wnt-signaling pathway. In addition, genetic disorders are involved in the development of the pathogenesis of osteoporosis. To identify osteoporosis, WHO recommends the use of dualenergy X-ray absorptive densitometry, which allows you to study the quantitative characteristics of bone tissue. Currently, there are various methods for evaluation of the quality of bone (microarchitectonics, the ability of bone tissue to be resistant to fracture), but these methods have limitations such as high cost and limited availability for their widespread using. The study of markers of bone remodeling in norm and in pathology helps to assess the quality of bone tissue indirectly, gives prospects in the selection of targeted therapy and improvement of early diagnosis of osteoporosis.